Analisis Penerapan Perencanaan Pajak (Tax Planning) dalam Upaya Penghematan Beban Pajak Penghasilan Badan pada PT DCM Tahun 2017 - Aditya Saputra (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This research aimed to discover whether tax planning implementation carried out at PT DCM could save corporate income tax expense. Qualitative method used as writing method which is method that collect, compile obtained data for subsequently interpreted and analyzed to provide complete information for problems solver. This research result is expected to provide information and suggestion for PT DCM that company could conduct tax planning as tax payment efficiency effort to gain maximum profit, but remain within tax regulation. Summary of this research revealed that tax planning implementation carried out by PT DCM could efficient payable tax expense. And company could save amounted to Rp.387.265.500,- from previous total payable taxThis research aimed to discover whether tax planning implementation carried out at PT DCM could save corporate income tax expense. Qualitative method used as writing method which is method that collect, compile obtained data for subsequently interpreted and analyzed to provide complete information for problems solver. This research result is expected to provide information and suggestion for PT DCM that company could conduct tax planning as tax payment efficiency effort to gain maximum profit, but remain within tax regulation. Summary of this research revealed that tax planning implementation carried out by PT DCM could efficient payable tax expense. And company could save amounted to Rp.387.265.500,- from previous total payable tax.